2023
DOI: 10.1021/acsami.3c00167
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Molecular Stacking via Tuning 2-Ethylhexyl Alkyl Chain Enables Improved Efficiency for All-Small-Molecule Organic Solar Cells

Abstract: There is always a dilemma between strong π−π stacking/ crystallinity and suitable domain size for all-small-molecule organic solar cells (ASM-OSCs), which puts forward higher requirements for the design of molecular donors. In this work, a series of novel molecular donors with different positional 2-ethylhexy (EH) attachments are designed and synthesized, named SM-R, SM-REH, SM-EH-R, and SM-EH-REH. It is found that EH-substitution on end groups (SM-REH) enables improved π−π interaction and crystallinity but wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…A shorter alkylthio group displayed a strong inclination toward crystallization, while a longer alkylthio group exhibited diminished crystallinity. Ge et al [94] also optimized the molecular stacking by 2-ethylhexyl alkyl chains in a series of donor materials. It has been demonstrated that the side chain length can significantly affect the PCE of OSCs.…”
Section: Challenges and Strategies To Improve Efficiencymentioning
confidence: 99%
“…A shorter alkylthio group displayed a strong inclination toward crystallization, while a longer alkylthio group exhibited diminished crystallinity. Ge et al [94] also optimized the molecular stacking by 2-ethylhexyl alkyl chains in a series of donor materials. It has been demonstrated that the side chain length can significantly affect the PCE of OSCs.…”
Section: Challenges and Strategies To Improve Efficiencymentioning
confidence: 99%
“…[1][2][3][4][5][6] With material innovation, device optimization, and mechanism studies, OSCs have witnessed significant progress in the past decade and achieved power conversion efficiencies (PCEs) of over 19% and 20% for single junction and tandem devices, respectively. [7][8][9][10][11][12][13][14][15][16] However, it is still a challenge to comprehend the relationship between the molecular structure of NFAs and their photovoltaic performance and to achieve a balance among the various parameters influencing the PCE of OSCs. [17][18][19] As one of the most successful NFAs, Y6 possesses a unique banana-like configuration with an A-DA′D-A architecture and achieved a PCE breakthrough of 15.7%.…”
Section: Introductionmentioning
confidence: 99%